7D.03: RELATIONSHIP BETWEEN AGE AND STRUCTURAL ALTERATIONS IN SUBCUTANEOUS SMALL RESISTANCE ARTERIES IN HYPERTENSIVE PATIENTS. (June 2015) - De Ciuceis, C.; Rossini, C.; Rosei, C. Agabiti; Sarkar, A.; Porteri, E.; La Boria, E.; Gavazzi, A.; Petroboni, B.; Pileri, P.; Rosei, E. Agabiti; Rizzoni, D.
Abstract : Objective: It was proposed that early vascular ageing may be an important mechanism of vascular damage in large conductance arteries. However it is not known whether aging may also affect small resistance artery morphology. Design and method: For this reason, we investigated 100 patients with essential hypertension. Secondary forms of hypertension were excluded according to standard clinical evaluations and biochemical or instrumental assessments. In all patients, an evaluation of small resistance arteries morphology was performed by a wire micromyographic approach (Mulvany's technique). A small amount of subcutaneous tissue was obtained by local biopsy or during election surgery and subcutaneous small resistance arteries were dissected and mounted on a myograph; the media to lumen ratio (M/L) was then measured. Results: The age range of our population was 22–81 years, with a mean value of 57 ± 12 years; 14% of them were current smokers, 32% had alterations in lipid patterns, none of them had diabetes mellitus, 58 were males and average blood pressure values were 156/95 ± 19/12 mmHg. We found a significant correlation between M/L and age (r = 0.30, p = 0.002): the statistical significance of the correlation persisted after correction for counfounding variables (gender, serum cholesterol, smoking status, serum glucose, systolic or diastolic blood pressure values). A statistically significant inverse correlation was also observed between internal diameter and age (r = -0.20, p = 0.046), while the correlation between age and media thickness did not reach statistical significance (r = 0.09, p = 0.37). Conclusions: Our data suggest that aging may affect microvascular structure in hypertensive patients. It is also possible that hypertension may anticipate the effects of physiological aging, and this should be explored in a relatively large population of normotensive subjects.